2022
DOI: 10.3390/ijms23042007
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Inhibition, Transport and Enhanced Transport via the Organic Cation Transporter 1

Abstract: The organic cation transporter 1 (OCT1, SLC22A1) transports a large number of structurally diverse endogenous and exogenous substrates. There are numerous known competitive and non-competitive inhibitors of OCT1, but there are no studies systematically analyzing the relationship between transport, stimulation, and inhibition. Here, we tested in vitro OCT1 inhibition by OCT1 substrates and transport of OCT1 inhibitors under uniform analytical conditions. Beyond inhibition testing with two model substrates, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
(99 reference statements)
3
19
0
Order By: Relevance
“…To extend our analyses on the selectivity of OCTs toward OCT1, we included averaged published data on OCT1 transport, and we also calculated averaged OCT2 and OCT3 data where additional published data were available. ,,,, In general, substrates of OCT1 had a higher molecular weight (MW) and a larger topological polar surface area (TPSA) (Table for a general overview comparing chemical descriptors between substrates of the OCTs, Figure S2 for histograms showing the distribution of TPSA and molecular weight for substrates of OCT1, OCT2, and OCT3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend our analyses on the selectivity of OCTs toward OCT1, we included averaged published data on OCT1 transport, and we also calculated averaged OCT2 and OCT3 data where additional published data were available. ,,,, In general, substrates of OCT1 had a higher molecular weight (MW) and a larger topological polar surface area (TPSA) (Table for a general overview comparing chemical descriptors between substrates of the OCTs, Figure S2 for histograms showing the distribution of TPSA and molecular weight for substrates of OCT1, OCT2, and OCT3).…”
Section: Resultsmentioning
confidence: 99%
“…But large-scale comparisons with different model substrates exist for OCT2 only. , Moreover, transporter substrates and inhibitors have been mainly characterized separately and rarely compared in the same study. Recently, we have shown that OCT1 substrates are mostly weak OCT1 inhibitors, but the relationship between substrate and inhibitor profiles has not been studied for the other OCTs so far. Lastly and most importantly, to our knowledge, there are no larger-scale substrate screenings for OCT3, limiting the comparison of substrate spectra across all three OCTs to heterogeneous data from many sources.…”
Section: Introductionmentioning
confidence: 92%
“…Intracellular concentrations of probe substrates and substrates-in-question were performed using HPLC-MS/MS analyses as essentially as described earlier [ 1 , 2 , 16 ]. Briefly, the cell lysate was centrifuged at 13,000 rpm in a tabletop centrifuge for 15 min to pellet potential cell debris.…”
Section: Methodsmentioning
confidence: 99%
“…More lipophilic substances may not only pass membranes by nonionic diffusion but also with these substances, influx and efflux transport may be significantly accelerated by membrane transporters. For several organic cations, organic cation transporters such as OCT1, OCT2, OCT3, OCTN1, OCTN2, THTR1, THTR2, MATE-1, MATE-2K and several others have been identified as relevant transporters [ 1 , 2 , 3 ]. However, these known transporters do not contribute in a relevant manner to the membrane transport of many cationic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation